Clinical Protocols for the Evaluation of Rod Function - Stingl, Krunoslav; Stingl, Katarina; Nowomiejska, Katarzyna; Kuehlewein, Laura; Kohl, Susanne; Kempf, Melanie; Strasser, Torsten; Jung, Ronja; Wilhelm, Barbara; Peters, Tobias; Kelbsch, Carina; Bartz-Schmidt, Karl Ulrich; et al. (Ophthalmologica (Basel), 2021)
This work presents a quick clinical protocol for dark-adapted chromatic (DAC) perimetry as well as a novel clinical tool, scotopic chromatic pupil campimetry (CPC). The goal of the study was to explore the applicability of these methods in a clinical setting, their test-retest repeatability, and the congruence of the results. Local rod sensitivity was assessed at 36 locations within 30° eccentricity of the visual field in 15 healthy subjects (mean age 43 ± 16 years; 7 females and 8 males) with DAC perimetry (red and cyan stimuli) and CPC 2 times in repeated measurements. The duration of individual measurements was 370 ± 5 s for CPC and 366 ± 62 s for DAC perimetry. The intraclass correlation (ICC) coefficient was 0.53 for DAC perimetry cyan stimuli, 0.67 for red stimuli, and 0.93 for CPC. However, the spatial resolution of CPC was substantially smaller than in DAC perimetry. We did not find a correlation of DAC perimetry and CPC measurements on the global or the local level. In comparison to DAC perimetry, CPC shows a superior intervisit repeatability in detecting functional changes in the rod population in an objective way with lower spatial resolution. Our results also indicate that these 2 methods measure the rod function in different ways and could thus constitute complementary scotopic functional diagnostics.